Efecto de la irradiación Gamma en frijol comén (Phaseolus vulgaris L.) - Granados V, R. (San Salvador (El Salvador), 1966)
Sumario (Es)
Ilus.; 12 ref.
Tesis (Ing Agr)
Keywords: PHASEOLUS VULGARIS; IRRADIACION GAMMA; MUTACION; FITOMEJORAMIENTO; SEMILLA; EL SALVADOR